Modern public finance: Theory and practice - Mahbob, Sulaiman (Universiti Utara Malaysia, 1998)
Book Title : Modern public finance: Theory and practice Author: D.M. Mithani Publisher: Himalaya Publishing House, Mumbai, India Year: 1998